Chronic non-communicable diseases in Argentina: Model and Forecast by sex and age - del Luján Tosello, Joana María (2022)
Chronic Non-Communicable Diseases (NCD) are diseases that are not transmitted from person to person and that are characterized by their generally slow evolution. In Argentina, NCDs are the main cause of death and disability, only two groups of causes (cardiovascular and cancer) are responsible for half of all deaths and 27 % of years of life potentially lost (YPLL). The general objective of this work, a quantitative, cross-sectional and descriptive study, is to describe and analyze the profile by age and sex of the mortality rates due to NCD in men and women in Argentina, based on the implementation of the model for functional data (MDF) by Hyndman and Ullah (2007). This model also makes it possible to forecast the behavior of mortality rates for both sexes, taking into account the changes related to age and the trend observed over time during the period 1985-2014. The relative difference in mortality between the beginning of the study period and the forecast for the year 2025 indicates that, if the prevailing behavior in rates continues, decreases of around 50 % would be achieved for men between 30 and 50 years of age. While for women the greatest decreases (of around 20 %) would be observed between the ages of 20 and 35. These results would indicate, in a more general way, that the behavior of the mortality rates of the age groups under 70 years, whose deaths are called “premature”, is of a clear decrease for both sexes, highlighting that, in the case of men, although they have higher NCD mortality rates, this decrease is more marked.